THE ARGUMENT-DRIVEN INQUIRY TRAINING FOR SCIENCE TEACHERS IN PALANGKA RAYA CITY - Ruli Meiliawati; Suandi Sidauruk; AT Siahaan (Jurusan Pendidikan Teknologi dan Kejuruan, FKIP, Universitas Palangkaraya, 2022)
Integrating laboratory activities with learning activities is a separate dynamic for science teachers, because learning science (Chemistry, Physics, and Biology) will be